Koszty produkcji mleka w polskich gospodarstwach należących do Europejskiego Stowarzyszenia Producentów mleka (EDF) w 2003 r. - Świtłyk, Michał (Milk Production Costs in 2003 in Polish Farms Belonging to the European Dairy Farmers, 2005)
In the paper the results of research on milk production costs in 2003 are presented. The research was conducted in the frames of the European Dairy Farmers. Researched population included 22 farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 355-359